Health Branding of #KFApp: The Ketofastosis Community Identity and Expression Strategy in Parodying the FaceApp Trend - Inge Salsabila Suryaman (Jobmark: Journal of Branding and Marketing Communication, 2021)
In promoting a healthy lifestyle, the Indonesian Ketofastosis community, through the Facebook group, put up the hashtag #KFApp or Ketofastosis Application. This hashtag satirizes the trending FaceApp phenomenon, where the application allows users to touch up their faces to look younger and more attractive. The message conveyed by the KFApp hashtag is that without touch-ups, we can have a youthful and attractive face through the Ketofastosis lifestyle (KFLS). KFLS Applies five pillars: consuming low-carbs, med-protein, and high-fat foods, being active and exercising, fasting on the windowsill intermittent, getting enough rest, and minimizing stress. This study uses the netnographic method to find strategies for identity, social movements, and cultural expressions among community members. This study is helpful as a strategic and academic reference on how health branding can be done in a fun way through a digital application meme strategy by taking advantage of the right momentum.